Improvement of Teacher Pedagogical Competence through In House Training Activities - fadil, akhmad; Aryani, Ine Kusuma (Universitas Muhammadiyah Purwokerto, 2021)
This study aims to determine the effect of In House Training (IHT) in increasing teacher pedagogical competence. Pedagogic competence is one of the teacher competencies which have an important vital role in achieving student learning outcomes quality. If the teacher's pedagogical competence is low, it may affect the learning outcomes of students. One of the efforts is through activities to increase teacher pedagogical competence. One of the activities to increase teacher competence is through training. The most effective and efficient competencies improvement training model is In House Training (IHT). This training can accommodate teacher training needs with easy access. The type of data used is secondary data. The method used in this research is the literature study method. The data obtained were collected, analyzed, and concluded to get conclusions about the literature study. Based on the research results, literature studies from several research results and journal articles show that In House Training activities can improve teacher pedagogical competence.